1994
DOI: 10.1289/ehp.94102s1195
|View full text |Cite
|
Sign up to set email alerts
|

Levels of non-ortho-substituted (coplanar), mono- and di-ortho-substituted polychlorinated biphenyls, dibenzo-p-dioxins, and dibenzofurans in human serum and adipose tissue.

Abstract: We have measured non-ortho-substituted (coplanar) polychlorinated biphenyl (PCB) levels as well as polychlorinated dibenzo-p-dioxin (PCDD) and polychlorinated dibenzofuran (PCDF) levels in human adipose tissue and serum collected in Atlanta, Georgia. The results show that the concentrations ofthe coplanar PCBs can be more than an order of magnitude higher than the concentrations of 2,3,7,8-tetrachlorodibenzo-p-dioxin. Our measurements in pooled serum collected in 1962, 1988, and 1969 show a decrease in coplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
2
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(47 citation statements)
references
References 42 publications
6
37
2
2
Order By: Relevance
“…It is noteworthy that two congeners of monoortho PCBs (PCB 118, PCB 156) individually contributed more to total TEQ than TCDD. Finally, consistent with that reported by others (Svensson et al, 1991;Patterson et al, 1994;Papke 1998;Kiviranta et al, 2002), we found that age was a significant predictor of Total TEQ in this Italian sample.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is noteworthy that two congeners of monoortho PCBs (PCB 118, PCB 156) individually contributed more to total TEQ than TCDD. Finally, consistent with that reported by others (Svensson et al, 1991;Patterson et al, 1994;Papke 1998;Kiviranta et al, 2002), we found that age was a significant predictor of Total TEQ in this Italian sample.…”
Section: Discussionsupporting
confidence: 93%
“…Also, the distribution of congeners was similar to that reported for other North American and European countries (Patterson et al, 1994;Papke 1998) with the four most prevalent analytes being OCDD,2,3,4,7,PCB 126,and PCB 169. We also found the four categories of compounds (PCDD, PCDFs, coplanar PCBs, mono-ortho-PCBs) contributed a roughly similar percent to Total TEQ (B25%).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Because coplanar PCBs are dioxinlike, these observations are relevant to PCB exposure as well. Some studies show that PCBs contribute more to toxic equivalents for dioxin than TCDD itself (155).…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Lipophilicity and resistance to degradation leads to bioaccumulation of these compounds in the food chain and in human adipose tissue, blood lipids and breast milk (Hansen, 1987;Patterson et al, 1994). PCBs and DDT analogs have been implicated as risk factors for breast cancer because of their potential to act as direct or indirect carcinogens (Safe, 1989;Ahlborg et al, 1995;Cogliano, 1998), their estrogenic and antiestrogenic properties (Bulger et al, 1983;McKinney and Waller, 1994;Brouwer et al, 1999), their ability to induce cytochrome p450 enzymes (Safe, 1994), and their alteration of mammary gland differentiation and proliferation (Brown and Lamartiniere, 1995).…”
Section: Introductionmentioning
confidence: 99%